2023
DOI: 10.1097/sla.0000000000004794
|View full text |Cite
|
Sign up to set email alerts
|

The AUGIS Survival Predictor: Prediction of Long-Term and Conditional Survival After Esophagectomy Using Random Survival Forests

Abstract: The aim of this study was to develop a predictive model for overall survival after esophagectomy using pre/postoperative clinical data and machine learning. Summary Background Data: For patients with esophageal cancer, accurately predicting long-term survival after esophagectomy is challenging.This study investigated survival prediction after esophagectomy using a Random Survival Forest (RSF) model derived from routine data from a large, well-curated, national dataset. Methods: Patients diagnosed with esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The relation between variables and OS probably is nonlinear for patients after LTx, and that may be the reason why the RSF model showed a better performance. In this study, we confirmed the superiority of the RSF model for LTx recipients compared with the Cox model, consistent with previous studies . Moreover, we also tried stepwise selection to determine the modeling factors for the Cox regression model.…”
Section: Discussionsupporting
confidence: 89%
“…The relation between variables and OS probably is nonlinear for patients after LTx, and that may be the reason why the RSF model showed a better performance. In this study, we confirmed the superiority of the RSF model for LTx recipients compared with the Cox model, consistent with previous studies . Moreover, we also tried stepwise selection to determine the modeling factors for the Cox regression model.…”
Section: Discussionsupporting
confidence: 89%
“…Chi-square tests were performed for categorical variables (e.g., gender) and differences in non-normally distributed numerical data using Wilcoxon rank-sum test between subgroups. To screen robust features, Elastic Net [a combination of Ridge and least absolute shrinkage and selection operator (LASSO) method], Random Forest, Boruta, and extreme gradient boosting (XGBoost) analyses were performed to select the most important subgroup-relevant features by calculating the importance score for each variable (Engebretsen and Bohlin, 2019;Johnson et al, 2020;Yperman et al, 2020;Colen et al, 2021;Rahman et al, 2021). With the remaining variables, the predictors were incorporated into a multivariable logistic regression model while adjusting for potential confounders including Age and Gender, considering the effect of participant structure on statistical results.…”
Section: Discussionmentioning
confidence: 99%
“…The Random Forest (RF) algorithm created decision trees with split points (nodes) as a result of recursive partitioning of the data into groups; tree branching was empirically based on variables that maximized outcome differences between daughter nodes until each tree was fully extended. The individual predicted probability was then derived using the average across all generated trees 21 . Specifically, an RF classification model was used to identify patient‐specific predictors of TTS = 0 adjusting for all patient, facility, tumor, and treatment characteristics 22 .…”
Section: Methodsmentioning
confidence: 99%